Varstvo otrokove koristi v postopku izvršbe in zavarovanja v zadevah glede varstva in vzgoje otrok ter osebnih stikov z otroki - Marolt, Nadja (Pravnik, 2015)
The article discusses the statutory regulations governing enforcement procedures in matters concerning the protection, upbringing and contacts with the child, jurisprudence of the Slovenian courts, of the ECHR and the ECJ in this field. Certain issues were raised, which the courts face when adjudicating in such matters. This area of law is not regulated in a single piece of legislation, but is rather fragmentarily regulated by the Enforcement and Securing of Civil Claims Act and the Marriage and Family Relations Act, whereby it should be noted that the nature and purpose of these two acts strongly oppose each other. In disputes with an international element, the courts must also decide in accordance with provisions of international conventions and the EU regulations. Such procedures require quick proceedings, which is particularly demonstrated when making decisions on the issuance of interlocutory injunctions. Courts with different material jurisdiction may decide on these interlocutory injunctions, which may not always be to the benefit of the child. In order to achieve a more efficient protection of the child's benefits, legislation could be amended so that the child who has already reached the age of 15 and who is capable of understanding the meaning and the legal consequences of its actions, as well as in enforcement proceedings, would be able to voice its opinion and thus "be heard" before the actual enforcement takes place.
Keywords: child; European Union; Evropska unija; izvršba; izvršilni postopek; otroci; sodne odločbe; starši; stiki; zavarovanje